People's Republic of China-Hong Kong Special Administrative Region : Staff Report for the 2006 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that Hong Kong Special Administrative Region has recovered strongly from a series of shocks in recent years and, as expected, the pace of growth is now moderating. Growth was 6.8 percent (year over year) in the first three quarters of 2006, somewhat slower than the 7.3 percent recorded in 2005. Inflation is expected to firm modestly with the tightening labor market and as rents adjust to previous increases in property prices. The current account surplus is expected to narrow with maturing external demand.